MOVE MORE DOUGLAS COUNTY: MOVING THROUGH STAGES OF CHANGE TOWARD DIABETES PREVENTION & MANAGEMENT - Alamos, Cristina (My University, 2025)
Type 2 diabetes is a major public health issue affecting millions in the United States, with many more at risk due to prediabetes. If left unaddressed, prediabetes often progresses to type 2 diabetes, further exacerbating this trend. In Kansas, the prevalence of type 2 diabetes and prediabetes highlights the urgent need for intervention. Symptoms, such as excessive thirst, hunger, dry skin, slow wound healing, and blurry vision, can develop gradually over years, often going unnoticed and leading to worse health outcomes. Regular screening is crucial for early detection and management to prevent serious complications, including heart disease, stroke, nerve damage, kidney disease, and vision loss. Beyond physical health, unmanaged diabetes can reduce quality of life and social well-being. However, with proper management through medication adherence, healthy dietary habits, and regular physical activity, individuals can lead full, healthy lives. Move More Douglas County, launched by LiveWell Douglas County in 2024, leverages the power of exercise in diabetes management. Guided by in the Transtheoretical Model of Behavior Change (TTM), the program increases access to physical activity opportunities for individuals with prediabetes and type 2 diabetes. Through a physical activity prescription from their healthcare provider, participants gain access to group fitness classes and personal training at local recreation centers at no additional cost. They also receive educational resources to support them through behavior change, habit formation, and progression through the stages of the TTM. By fostering sustainable physical activity habits, Move More Douglas County aims to improve diabetes management and overall health outcomes in the community.
Keywords: Prediabetes; Type 2 Diabetes; Physical activity; Transtheoretical model (TTM); Douglas county; Public health